Integrasi Kurikulum Kewirausahaan dalam Pendidikan Pesantren Sebagai Upaya Mencetak Santripreneur - Qistin toniyah Zamrud (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
This study examines the integration of the entrepreneurship curriculum at Pondok Darul Hijrah Buntet Pesantren Cirebon as an effort to produce santripreneurs*, driven by the need to transform pesantren into centers for student economic empowerment. Using a qualitative case study approach, data were collected through observation, interviews, documentation, and questionnaires involving leaders, teachers, business unit managers, and 60 final-year students, and analyzed using the Miles and Huberman model. The findings indicate both intracurricular integration through entrepreneurship subjects and extracurricular integration through practical business activities; 82% of students reported improved practical skills, and 65% expressed interest in starting a business after graduation—indicating the program’s effectiveness in fostering motivation and entrepreneurial readiness. These results affirm that the entrepreneurship curriculum effectively shapes santripreneurs and can serve as a sustainable model for Islamic-based economic education.